PRINCIPLES OF THE CURRENT ORGANIZATION AND ARRANGEMENT OF PRIMARY SCHOOLS IN THE RAŠKA REGION (1912 - 2025) - Šehović, Sefedin; Trtovac Dedeić, Alma; Prušević Sadović, Filduza (Metodička teorija i praksa, 2026)
The subject of research in this paper was related to the principles of the current organization and arrangement of elementary schools in the Raška region (1912-2025). The topic of the paper enters the domain of searching for the essential conditions of elementary schools at one time and for a critical analysis of the position of elementary schools in one part of Serbia in its education system. The meaning of this study enables us to see the principles or principles for establishing, organizing and arranging the elementary school in the Raš area, in accordance with that organization elsewhere, in the surrounding parts of this part of Serbia and other countries. Precisely for the indicated reasons, one of the priorities in the thematization of the content of this work are the principles on which an elementary school can be arranged and organized in a part of the underdeveloped area of Serbia.